2010
DOI: 10.1111/j.1469-8137.2010.03220.x
|View full text |Cite
|
Sign up to set email alerts
|

Birch (Betula spp.) leaves adsorb and re‐release volatiles specific to neighbouring plants – a mechanism for associational herbivore resistance?

Abstract: Summary• Plant-emitted semi-volatile compounds have low vaporization rates at 20-25°C and may therefore persist on surfaces such as plant foliage. The passive adsorption of arthropod-repellent semi-volatiles to neighbouring foliage could convey associational resistance, whereby a plant's neighbours reduce damage caused by herbivores.• We found that birch (Betula spp.) leaves adsorb and re-release the specific arthropod-repelling C 15 semi-volatiles ledene, ledol and palustrol produced by Rhododendron tomentosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
198
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(207 citation statements)
references
References 51 publications
(138 reference statements)
7
198
2
Order By: Relevance
“…Considering the green area index for the grassland, which increased from 5.6 m 2 m −2 to 6.6 m 2 m −2 during the period of interest, the measured peak deposition values ranged between 3.3 nmol m −2 s −1 and 3.9 nmol m −2 s −1 on a green area basis, which compares well with the range of values reported by Noe et al [2008]. Himanen et al [2010] found further evidence for an uptake and rerelease of terpenes by nonemitting plants that grow intermixed with emitting species in a natural environment. Further work is required to quantify the contribution of various sinks, e.g., stomatal uptake, chemical losses or scavenging to the soil, to the deposition of monoterpenes observed in this study.…”
Section: Deposition Fluxes Of Monoterpenessupporting
confidence: 81%
“…Considering the green area index for the grassland, which increased from 5.6 m 2 m −2 to 6.6 m 2 m −2 during the period of interest, the measured peak deposition values ranged between 3.3 nmol m −2 s −1 and 3.9 nmol m −2 s −1 on a green area basis, which compares well with the range of values reported by Noe et al [2008]. Himanen et al [2010] found further evidence for an uptake and rerelease of terpenes by nonemitting plants that grow intermixed with emitting species in a natural environment. Further work is required to quantify the contribution of various sinks, e.g., stomatal uptake, chemical losses or scavenging to the soil, to the deposition of monoterpenes observed in this study.…”
Section: Deposition Fluxes Of Monoterpenessupporting
confidence: 81%
“…8 Three R. tomentosumspecific semi-volatiles (ledol, palustrol and ledene) formed 24.5 ± 6.6% and 16.1 ± 7.9% of the total terpenoids emitted by two birch species, B. pendula and B. pubescens, respectively, when they were exposed to neighboring R. tomentosum in articLe addendum articLe addendum farming. 10 A recent meta-analysis 11 on factors leading to differences in insect responses towards volatiles (e.g., attraction versus repellence) revealed that factors including the sex, feeding guild, taxonomic group and diet breadth of insects can be used to explain patterns of behavior.…”
mentioning
confidence: 99%
“…8 Thus, wider screens to test the effectiveness of R. tomentosum specific semi-volatiles against various insects and also important agricultural pests, would help reveal their exploitation potential e.g., for pest control in organic a field set-up (B. pendula) or in a natural habitat (B. pubescens) (Fig. 1).…”
mentioning
confidence: 99%
“…Both of these processes have been demonstrated to have ecological significance in field studies. 3,4,10 The reactions of volatile chemicals with pollutants can influence both processes in different ways. It is most likely that the active process will be rendered ineffective, while the passive process may be more complexly altered with volatile Figure 1.…”
mentioning
confidence: 99%
“…10,11 The active process is where the receiver plant actively changes in response to a signal, for example gene activation 2,12 or increased production of extra-floral nectar (EFN). 4 This is true plant-plant signaling involving perception of a signal.…”
mentioning
confidence: 99%